2003
DOI: 10.1007/s00464-002-8718-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-port versus four-port laparoscopic cholecystectomy

Abstract: Two-port laparoscopic cholecystectomy resulted in less individual port-site pain and similar clinical outcomes but fewer surgical scars compared to four-port laparoscopic cholecystectomy. Thus, it can be recommended as a routine procedure in elective laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 9 publications
3
93
1
1
Order By: Relevance
“…We used four 5-mm ports, whereas Kim et al [10] used one 12-mm trocar and two 5-mm trocars, and Tsimoyiannis et al [11] made four punctures in the abdomen, using one 11-mm trocar and three 5-mm trocars. Several studies showed that either the size or the number of ports related to the degree of postoperative pain [12][13][14]. Therefore, the differences in both the size and the number of trocars may be a factor that caused disparity between the results.…”
Section: Discussionmentioning
confidence: 99%
“…We used four 5-mm ports, whereas Kim et al [10] used one 12-mm trocar and two 5-mm trocars, and Tsimoyiannis et al [11] made four punctures in the abdomen, using one 11-mm trocar and three 5-mm trocars. Several studies showed that either the size or the number of ports related to the degree of postoperative pain [12][13][14]. Therefore, the differences in both the size and the number of trocars may be a factor that caused disparity between the results.…”
Section: Discussionmentioning
confidence: 99%
“…The only reported advantage of single incision laparoscopic surgery (SILS) over standard laparoscopic cholecystectomy is an improved cosmetic result. 7 With gradual and long experience in laparoscopy surgery, now three port LC is routinely performed by experienced surgeon. Multiple study reports that three port LC is safe when performed by experienced surgeons.…”
Section: Reason Tomentioning
confidence: 99%
“…6,7 Although, three port cholecystectomy is not common, research has demonstrated that it is a safe and feasible surgical technique. 7,8 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The patient was a 75-year-old male (body mass index (BMI) 20.1 kg/m 2 ; height 167 cm, weight 56 kg) with sigmoid colon adenocarcinoma. He had no history of previous surgery or underlying disease but leukoplakia.…”
Section: Case Reportmentioning
confidence: 99%